Exploration Strategy Related Design Considerations of WSN-Aided Mobile Robot Exploration Teams - Tuna, Gurkan; Gulez, Kayhan; Gungor, Vehbi Cagri; Mumcu, Tarik Veli (SPRINGER-VERLAG BERLIN, 2012)
This paper presents a novel approach to mobile robot exploration. In this approach, mobile robots send their local maps to the central controller and coordinate with each other using a wireless sensor network (WSN). Different from existing rendezvous point-based exploration strategies, the use of a WSN as the communication media allows quick and cost-effective exploration and mapping of an unknown environment. Overall, this paper introduces WSN-aided mobile robot exploration strategy and shows comparative performance evaluations using the Player/Stage simulation platform. Here, our main goal is to present potential advantages of WSN-aided mobile robot exploration for Simultaneous Localization and Mapping (SLAM).
Keywords: Mobile Robot Exploration Teams; WSNs; Exploration Strategy; Player/Stage; REAL-TIME; SIMULTANEOUS LOCALIZATION; MULTIROBOT EXPLORATION; WIRELESS SENSOR; Computer Science